THE IMPACT OF DIFFERENTIATED INSTRUCTION USING A TRAINING METHOD TO DEVELOP SOME BASIC SKILLS IN FUTSAL FOR FOURTH-YEAR MIDDLE SCHOOL STUDENTS - M. Dr. Omar Latofi Majeed (Proximus Journal Publishing, 2025)
The study aimed to use the learning method by group competition and cooperative learning in developing some basic football skills for the research sample. The research sample was divided into three groups, each group consisted of 20 students from the research community. The researcher concluded that the group competition method and the cooperative learning method are two effective methods in learning some basic skills in football. As it turned out, there is a lack of interest on the part of educational bodies in using advanced methods in physical education lessons. The competitive learning method appeared to be the most effective cooperative method in learning some basic football skills.
Keywords: collective competition; cooperative competition